Des tranchées à la mangrove : Généalogies poétiques de la Grande Guerre à la "guerre du Biafra" - Nelly Segers (Caliban: French Journal of English Studies)
The Nigerian Civil war broke out in 1967 a few years after independence. It lasted up to January 1970. It inspired many soldiers, whether students or confirmed writers. They fought on both sides or like Wole Soyinka, tried to find a third way to solve the conflict. The violence they met inspired poems which may be linked to the War Poets of 1914-1918. The influence of the British poets on Nigerian writers takes its roots in history, Nigeria being a British colony until 1960. But this inheritance has not only to do with similar degree courses in universities. It is also related to the nature of both conflicts of unprecedented violence with soldiers facing terrifying scenes leading them to disenchantment. Unsurprisingly, their poetry expresses common themes and images, springing from the intense feeling of the uselessness of so many massacre.